Interleukin-6 Trans-Signaling Pathway Promotes Immunosuppressive Myeloid-Derived Suppressor Cells via Suppression of Suppressor of Cytokine Signaling 3 in Breast Cancer - Jiang, Mengmeng; Chen, Jieying; Zhang, Wenwen; Zhang, Rui; Ye, Yingnan; Liu, Pengpeng; Yu, Wenwen; Wei, Feng; Ren, Xiubao; Yu, Jinpu (Frontiers in Immunology, 2017)
Interleukin-6 (IL-6) has been reported to stimulate myeloid-derived suppressor cells (MDSCs) in multiple cancers, but the molecular events involved in this process are not completely understood. We previously found that cancer-derived IL-6 induces T cell suppression of MDSCs in vitro via the activation of STAT3/IDO signaling pathway. In this study, we aimed to elucidate the underlying mechanisms. We found that in primary breast cancer tissues, cancer-derived IL-6 was positively correlated with infiltration of MDSCs in situ, which was accompanied by more aggressive tumor phenotypes and worse clinical outcomes. In vitro IL-6 stimulated the amplification of MDSCs and promoted their T cell suppression ability, which were fully inhibited by an IL-6-specific blocking antibody. Our results demonstrate that IL-6-dependent suppressor of cytokine signaling 3 (SOCS3) suppression in MDSCs induced phosphorylation of the JAK1, JAK2, TYK2, STAT1, and STAT3 proteins, which was correlated with T cell suppression of MDSCs in vitro. Therefore, dysfunction in the SOCS feedback loop promoted long-term activation of the JAK/STAT signaling pathway and predominantly contributed to IL-6-mediated effects on MDSCs. Furthermore, IL-6-induced inhibition of SOCS3 and activation of the JAK/STAT pathway was correlated with an elevated expression of IL-6 receptor α (CD126), in which the soluble CD126-mediated IL-6 trans-signaling pathway significantly regulated IL-6-mediated effects on MDSCs. Finally, IL-6-induced SOCS3 dysfunction and sustained activation of the JAK/STAT signaling pathway promoted the amplification and immunosuppressive function of breast cancer MDSCs in vitro and vivo, and thus blocking the IL-6 signaling pathway is a promising therapeutic strategy for eliminating and inhibiting MDSCs to improve prognosis.